KEPEMIMPINAN HIJAU BERBASIS KECERDASAN BUATAN DALAM PENDIDIKAN TEKNIK DAN KEJURUAN: JALAN MENUJU SDGS 2030 - Yuberta, Andre; Giatman, M.; Lapisa, Remon; Maksum, Hasan (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The transformation of vocational education in the digital era requires a new leadership paradigm capable of integrating Artificial Intelligence (AI) with sustainability principles. This study highlights the importance of green leadership in managing TVET institutions to align with the 2030 Sustainable Development Goals, particularly those related to quality education, decent work and economic growth, as well as innovation and infrastructure. The main objective of this research is to formulate a conceptual model of AI-driven green leadership as a strategic pathway for sustainable transformation in vocational institutions. This research employs a mixed-methods approach with a sequential explanatory design. The quantitative phase involved 148 respondents from 12 vocational institutions in Indonesia using a Likert-scale questionnaire to measure perceptions of green leadership, digital readiness, and AI adoption. Data were analyzed using SEM-PLS and further explored through in-depth interviews with 15 institutional leaders as part of the qualitative phase. The results indicate that AI utilization significantly enhances decision-making efficiency, organizational transparency, and green innovation within the TVET environment. Leadership that combines digital intelligence and ecological awareness fosters an adaptive and sustainable organizational culture. The research implies the necessity of policies that promote AI-based green leadership literacy, the development of sustainable digital leadership curricula, support for environmentally friendly data infrastructure, and cross-sector partnerships to ensure that technological innovation aligns with human development and environmental sustainability.Keyword: green_leadership; artificial_intelligence; SDGs.Abstrak: Transformasi pendidikan vokasi di era digital membutuhkan kepemimpinan baru yang mampu mengintegrasikan kecerdasan buatan (AI) dengan prinsip keberlanjutan. Penelitian ini menyoroti pentingnya kepemimpinan hijau dalam pengelolaan TVET agar selaras dengan SDGs 2030, terutama tujuan terkait pendidikan bermutu, pekerjaan layak, dan inovasi. Tujuan utama penelitian adalah merumuskan model konseptual AI-driven green leadership sebagai strategi transformasi berkelanjutan di institusi vokasi. Metode yang digunakan adalah mixed methods dengan desain sekuensial eksplanatori. Tahap kuantitatif melibatkan 148 responden dari 12 institusi vokasi di Indonesia melalui kuesioner skala Likert yang mengukur persepsi kepemimpinan hijau, kesiapan digital, dan adopsi AI. Analisis data menggunakan SEM-PLS, kemudian diperdalam melalui wawancara dengan 15 pemimpin institusi pada tahap kualitatif. Hasil penelitian menunjukkan bahwa pemanfaatan AI meningkatkan efisiensi pengambilan keputusan, transparansi organisasi, serta inovasi hijau di lingkungan TVET. Kepemimpinan yang menggabungkan kecerdasan digital dan kesadaran ekologis mampu menciptakan budaya organisasi yang adaptif dan berkelanjutan. Implikasi penelitian menegaskan pentingnya kebijakan yang mendorong literasi kepemimpinan hijau berbasis AI, pengembangan kurikulum kepemimpinan digital berkelanjutan, dukungan infrastruktur data ramah lingkungan, serta kemitraan lintas sektor untuk memastikan inovasi teknologi sejalan dengan pembangunan manusia dan lingkungan.Kata kunci: kepemimpinan_hijau; kecerdasan_buatan; SDGs